Predictors and outcomes of increases in creatine phosphokinase concentrations or rhabdomyolysis risk during statin treatment - van Staa, Tjeerd P (Br J Clin Pharmacol, 2014)
AIM: The aim was to evaluate clinical risk factors associated with myotoxicity in statin users. METHODS: This was a cohort study of patients prescribed a statin in UK primary care practices contributing to the Clinical Practice Research Datalink. Outcomes of interest were creatine phosphokinase (CPK) concentrations and clinical records of rhabdomyolysis. RESULTS: The cohort comprised 641 703 statin users. Simvastatin was most frequently prescribed (66.3%), followed by atorvastatin (24.4%). CPK was measured in 127 209 patients: 81.4% within normal range and 0.7% above <four times the upper limit of normal (ULN). Rhabdomyolysis was recorded in 59 patients. Patients with concomitant prescribing of CYP3A4-interacting drugs had an increased odds ratio (OR) of rhabdomyolysis compared with controls (OR 3.71, 95% CI 1.18, 11.61) and >four times ULN CPK compared with normal CPK (OR 1.28, 95% CI 1.01, 1.60). Rosuvastatin users had higher risk of >four times ULN CPK (OR 1.62, 95% CI 1.22, 2.15) as did patients with larger daily doses of other statin types. A recent clinical record of myalgia was associated with an increased OR of >four times ULN CPK (OR 1.73, 95% CI 1.37, 2.18). In patients who were rechallenged to statins and had repeat CPK measurements after >four times ULN CPK abnormalities, 54.8% of the repeat CPK values were within normal range, 32.1% between one to three times and 13.0% >four times ULN. CONCLUSIONS: The frequencies of substantive CPK increases and rhabdomyolysis during statin treatment were low, with highest risks seen in those on large daily doses or interacting drugs and on rosuvastatin. CPK measurements appeared to have been done in a haphazard manner and better guidance is needed.